Pengaruh Harga dan Kualitas Pelayanan terhadap Kepuasan Klien pada PT Bina Nusa Teknik - Tarmadi, Jajang; Mubarok, Dadan Abdul Azizi (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study aims to describe client satisfaction, price, and service quality and analyze the effect of price and service quality on client satisfaction at PT Bina Nusa Teknik. Using quantitative methods with descriptive and verification approaches, samples were taken through total sampling involving 35 PT Bina Nusa Teknik clients, with data collected through questionnaires. Data analysis includes multiple linear regression, correlation coefficient, and determination coefficient. Descriptive analysis shows a client satisfaction score of 1,188 (moderate), price of 825 (high), and service quality of 1,302 (high). The study's results revealed that price affects client satisfaction with a correlation of 0.808, and service quality affects client satisfaction with a correlation of 0.842. Simultaneously, price and service quality affect client satisfaction with a simultaneous correlation of 0.912 and a contribution of influence of 83.2%.